(untitled) (TAMADDUN NURI JURNALI, 2024)
the author examines the Conception of the perfect man in the philosophy of Ibn Sina, highlighting it as an important aspect in both mystical and philosophical teachings. The model of the ideal man, created by Ibn Sina’s representation, is intellectual harmony, moderation and moral beauty, reflecting the high ideals of cognition and consciousness.